Cultural Heritage: Changing Ideas on Compensation in Planning - Rönn, Magnus; Danielsson, Benjamin Grahn; Swedberg, Stig (Architectural Research in Finland, 2017)
Compensation measures are a new method for handling impact on cultural heri-tage in land use planning. The idea with compensation measures can be understood as an extension of the polluter pays principle. Today, compensation measures are mainly used when natural environments are damaged by deve-lopment, but it is also possible to use compensation measures when a project results in negative impact on cultural heritage. However, there is a lack of ex-perience in using compensation when it comes to the latter. In our work as heritage consultants, we have experienced difficulties in imple-menting compensation measures in projects and assignments. Since 2013, we have organised a research project dealing with compensation measures and cultural heritage; aiming towards a new practice and better use of planning in-struments. With this paper, we want to share our results from four case studies where development impact on cultural heritage has led to discussions about, and implementation of, compensation measures, find patterns in the use of compensation measures in planning processes. The results show an uncertain-ty in understanding compensation as a concept. This is due to an absence of practice dealing with compensation measures; cultural heritage values are not addressed in a proper way in negotiations over land access. Several instruments for compensation measures in planning processes can actually be found in the law and land use of the Swedish planning system, but they are not being used properly, which results in a negative impact on the cultural heritage. After two years of analysing and discussing our case studies in workshops and conferences, we have concluded that there is a strong need for clarifying planning instruments and for developing a professional practice dealing with compensation measures.
Keywords: cultural heritage; compensation; planning; values; impact; planning instruments